THE EFFECTIVENESS OF ARTIFICIAL HOOK COLOR ON POLE AND LINE OPERATION IN TERNATE WATERS, NORTH MALUKU - Danu Sudrajat; Rahmat Mualim; Derdly Rahaningmas; Muhammad Handri; Muhammad Hery Riyadi Alauddin; Yusrizal Yusrizal (Politeknik Kelautan dan Perikanan Dumai, 2023)
Skipjack tuna (Katsuwonus pelamis) is a large pelagic fish that seeks prey using the sense of sight, so the color of the hook used must be able to attract the attention of skipjack to eat the hook. The purpose of this research is to determine the effect of hook color on pole and line catches. The colors of the hook used are red, green and silver. The analysis used to see differences in skipjack catches based on hook color used two analyzes, namely comparative descriptive and statistical. Comparative descriptive analysis was carried out on the composition of pole and line catches. Statistical test using completely randomized design (CRD). The results showed that the hooks that produced the most skipjack tuna were red with 1785 fish or 57% of the total catch, then green with 830 fish (26%) and silver with 513 (17%) catches. Based on the CRD ANOVA statistical test, the average difference in catches based on hook color was significantly different with a significance value less than 0.05 (0.00<0.05), which means the catches of the 3 hook colors were significantly different. From the catch data, the hook color that gets the most catches is the red hook.